2021
DOI: 10.1088/1755-1315/797/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cages dimension to the growth of giant trevally Caranx ignobilis

Abstract: Fish growth is one of the most target in aquaculture with right method of feeding, water quality and size of cages where they were held. In this study, a 70-day research was conducted to evaluate the effect of floating net cages dimension on growth and survival of trevally Caranx ignobilis in Ambon Inner Bay of Indonesia. A total of 90 juvenile trevallies with an average weight of 17.18 ± 1.9 g was randomly stocked in six floating net cages at three different sizes as treatments in replicate groups. Fish were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Lethrinids had having a body length of 27.83 mm and a mass of 0.276 g [13]. Caranx ignobilis weight was in the range of 213.8 ± 23.6 -181.7 ± 31.5 g in fish cages (karamba) [14]. Developmental studies revealed that the spawning process occurs once a year and carnivorous feeding [6].…”
Section: Results and Analysismentioning
confidence: 99%
“…Lethrinids had having a body length of 27.83 mm and a mass of 0.276 g [13]. Caranx ignobilis weight was in the range of 213.8 ± 23.6 -181.7 ± 31.5 g in fish cages (karamba) [14]. Developmental studies revealed that the spawning process occurs once a year and carnivorous feeding [6].…”
Section: Results and Analysismentioning
confidence: 99%